Talking through the crisis: social dialogue and industrial relations trends in selected EU countries (Geneva, 2017)
"Social dialogue between government, employers’ and workers’ organizations is a powerful tool for correcting labour market imbalances and promoting jobs-rich economic recovery. During and since the economic and financial crisis which started in 2008, national social dialogue institutions in countries of the European Union (EU) have been tested but, in many cases, have demonstrated their potential to innovate and contribute to a return to positive growth.